The Efficiency of Sclerotherapy in the Treatment of Vascular Malformations: A Retrospective Study of 63 Patients - Esko Veräjänkorva; Riitta Rautio; Salvatore Giordano; Ilkka Koskivuo; Otto Savolainen (Hindawi Publishing Corporation, 2022)
Background and Aims. Vascular malformations are a vast group of congenital malformations that are present at birth. These malformations can cause pain, pressure, and cosmetic annoyance as well as downturn growth and development in a child in the case of high flow. Sclerotherapy has become an important tool in the treatment of vascular malformations. However, little is known about the success rate of sclerotherapy.
Material and Methods. In this study, the efficiency of sclerotherapy in the treatment of vascular anomalies was investigated retrospectively in 63 patients treated in Turku University Hospital between 2003 and 2013.
Results. Out of the 63 patients investigated, 83% (53) had venous malformations (VMs) and 9% (5) were defined as having arteriovenous malformations (AVMs). Patients with a VM were operated on, in 14% (8) out of all VM cases. Hence 86% (45) of patients with a VM received adequate help to their symptoms solely from sclerotherapy. The duration of treatment for the 14% of the VM patients that needed a surgical procedure was prolonged by 7–9 months, that is, by 41%.
Conclusions. Sclerotherapy is an effective method in the treatment of VMs with a satisfactory clinical response in patients symptoms in 84% of cases.